MANAGEMENT SYSTEM FOR STREAMLINING THE INNOVATION PROCESS OF RESEARCH AND DEVELOPMENT WORKPLACE - Husarova, Martina; Spisak, Jan (European Scientific Journal, ESJ, 2013)
Innovation is the application of new knowledge and its materialization. Thus it ensures the company’s ability to cope with changes in the business environment and the ability to survive in the global competitive environment. As a result, innovation saves natural resources, provides safe and more efficient transport and production. Innovations change the style of work life, place emphasis on the importance of education, creativity, communication and collaboration. However, innovations are associated with a number of problems. They require high costs of the research and development and they face the risks during implementation. This paper describes specific experience with the application of principles and tools of logistics, project management and mainly the application of management system created for the streamlining not only the process of preparation and implementation of the specific innovation project, but also for the streamlining the operation of research and development workplace which implement innovative projects.